Outcomes of Pediatric Patients With Defibrillators Following Initial Presentation With Sudden Cardiac Arrest. (February 2021) - Robinson, Jeffrey A.; LaPage, Martin J.; Atallah, Joseph; Webster, Gregory; Miyake, Christina Y.; Ratnasamy, Christopher; Ollberding, Nicholas J.; Mohan, Shaun; Von Bergen, Nicholas H.; Johnsrude, Christopher L.; Garnreiter, Jason M.; Spar, David S.; et al.
Abstract : Background: Implantable cardioverter defibrillators (ICD) are recommended for secondary prevention after sudden cardiac arrest (SCA). The outcomes of pediatric patients receiving an ICD after SCA remain unclear. The objective of this study is to evaluate outcomes, future risk for appropriate shocks, and identify characteristics associated with appropriate ICD therapy during follow-up. Methods: Multicenter retrospective analysis of patients (age ⩽21 years) without prior cardiac disease who received an ICD following SCA. Patient/device characteristics, cardiac function, and underlying diagnoses were collected, along with SCA event characteristics. Patient outcomes including complications and device therapies were analyzed. Results: In total, 106 patients were included, median age 14.7 years. Twenty (19%) received appropriate shocks and 16 (15%) received inappropriate shocks (median follow-up 3 years). First-degree relative with SCA was associated with appropriate shocks ( P <0.05). In total, 40% patients were considered idiopathic. Channelopathy was the most frequent late diagnosis not made at time of presentation. Neither underlying diagnosis nor idiopathic status was associated with increased incidence of appropriate shock. Monomorphic ventricular tachycardia (hazard ratio, 4.6 [1.2–17.3]) and family history of sudden death (hazard ratio, 6.5 [1.4–29.8]) were associated with freedom from appropriate shock in a multivariable model (area under the receiver operating characteristic curve, 0.8). Time from diagnoses to evaluation demonstrated a nonlinear association with freedom from appropriate shock ( P =0.015). In patients >2 years from implantation, younger age ( P =0.02) and positive exercise test ( P =0.04) were associated with appropriate shock. Conclusions: The risk of future device therapy is high in pediatric patients receiving an ICD after SCA, irrelevant of underlying disease. Lack of a definitive diagnosis after SCA was not associated with lower risk of subsequent events and does not obviate the need for secondary prophylaxis. Abstract : Supplemental Digital Content is available in the text.